A Rare Case Report: Bilateral Choanal Atresia in an Adult Patient - Kars, Ayhan; Bingöl, Fatih; Atalay, Fatma (AVES YAYINCILIK A.Ş., 2020)
Posterior choanal atresia is rare but is the most common congenital malformation of the nasal cavity. It is characterized by a completely closed choana. Generally, this malformation is observed in newborns as increased respiratory distress during feeding, cyanotic attacks, and relaxation with crying. In contrast to unilateral atresia, bilateral disease is a life threatening condition and is extremely rare in adults. Herein, we presented a case of bilateral membranous choanal atresia detected in an 18-year-old patient. An 18-year-old female patient was admitted to our clinic after complaining of nasal obstruction, nasal discharge, snoring, anosmia, and mouth breathing since she was a child. On endoscopic examination, a right-deviated nasal septum and bilaterally closed choanae were observed. Membranous bilateral choanal atresia was observed on computed tomography (CT). The patient underwent transnasal endoscopic surgery under general anesthesia. Both septoplasty and bilateral coanoplasty surgeries were performed. No complications were observed postoperatively or at one year of follow up. Bilateral choanal atresia is a rare anomaly in adults. The diagnosis can easily be made by endoscopic examination or CT. The transnasal endoscopic surgical technique is an easy, reliable, and effective treatment method. © Author(s).
Keywords: Adult; nasal obstruction; stent; bilateral choanal atresia; Immunologic diseases. Allergy; RC581-607